Hto, Tritiated Amino Acid Exposure and External Exposure Induce Differential Effects on Hematopoiesis and Iron Metabolism - Jean-Marc Bertho (Nature Portfolio, 2019)
Abstract The increased potential for tritium releases from either nuclear reactors or from new facilities raises questions about the appropriateness of the current ICRP and WHO recommendations for tritium exposures to human populations. To study the potential toxicity of tritium as a function of dose, including at a regulatory level, mice were chronically exposed to tritium in drinking water at one of three concentrations, 10 kBq.l−1, 1 MBq.l−1 or 20 MBq.l−1. Tritium was administered as either HTO or as tritiated non-essential amino acids (TAA). After one month’s exposure, a dose-dependent decrease in red blood cells (RBC) and iron deprivation was seen in all TAA exposed groups, but not in the HTO exposed groups. After eight months of exposure this RBC decrease was compensated by an increase in mean globular volume - suggesting the occurrence of an iron deficit-associated anemia. The analysis of hematopoiesis, of red blood cell retention in the spleen and of iron metabolism in the liver, the kidneys and the intestine suggested that the iron deficit was due to a decrease in iron absorption from the intestine. In contrast, mice exposed to external gamma irradiation at equivalent dose rates did not show any change in red blood cell numbers, white blood cell numbers or in the plasma iron concentration. These results showed that health effects only appeared following chronic exposure to concentrations of tritium above regulatory levels and the effects seen were dependent upon the speciation of tritium.